2023
DOI: 10.3390/molecules28020743
|View full text |Cite
|
Sign up to set email alerts
|

Design of Nickel Supported Hierarchical ZSM-5/USY Zeolite Bifunctional Catalysts for One-Pot Menthol Synthesis via Liquid-Phase Citral Hydrogenation

Abstract: Nickel-supported hierarchical zeolite catalysts were prepared through a desilication reassembly process under optimized conditions and applied in one-pot menthol synthesis. In this work, the hierarchical zeolite-supported metal bifunctional catalysts were prepared with the help of desilication re-assembly and wetness impregnation techniques and applied in menthol synthesis via citral hydrogenation. The prepared catalysts were characterized using PXRD, BET, FE-TEM, NH3-TPD, H2-TPR, pyridine adsorption, and ICP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The results showed that the impregnation technique had caused a rise in the catalyst's acidity, resulting from Ir molecules interacting with the zeolite framework. This behavior might be explained by closing pores and neutralizing acidic sites within the pores [62]. The smaller kinetic diameter of the Ir ion (close to 0.82 Å) allows it to enter the ZSM-5 channels (as much as 5.5 Å), leading to interactions with internal acidic sites.…”
Section: Characteristics Of Catalystmentioning
confidence: 99%
“…The results showed that the impregnation technique had caused a rise in the catalyst's acidity, resulting from Ir molecules interacting with the zeolite framework. This behavior might be explained by closing pores and neutralizing acidic sites within the pores [62]. The smaller kinetic diameter of the Ir ion (close to 0.82 Å) allows it to enter the ZSM-5 channels (as much as 5.5 Å), leading to interactions with internal acidic sites.…”
Section: Characteristics Of Catalystmentioning
confidence: 99%